Clinical Approach to Recurrent Hemoptysis Due to Pulmonary Mycosis: A Case Study of Aspergillus Fumigatus and Candida Albicans Infections - Amiruddin, Amiruddin (Universitas Pahlawan Tuanku Tambusai, 2025)
Recurrent hemoptysis caused by pulmonary mycosis from Aspergillus fumigatus and Candida albicans infection presents a complex clinical challenge, particularly in patients with a history of pulmonary tuberculosis. This case study examines clinical characteristics, radiological findings, microbiological results, and responses to antifungal therapy, bronchial artery embolization, and lobectomy. The findings indicate that a comprehensive diagnostic and therapeutic approach effectively controls hemoptysis and improves patient outcomes despite risks of complications such as anemia and secondary infections. The study highlights the importance of integrated management and long-term monitoring to enhance clinical outcomes and reduce hemoptysis recurrence in pulmonary mycosis.